360° management competency assessment: is our understanding adequate?. (12th February 2016) - Liang, Zhanming; Howard, Peter F; Leggat, Sandra G
Abstract : Management competence links positively to organisational success and efficient and safe healthcare service delivery. A newly developed 360° management competency assessment tool was used to assess 68 middle level managers working in the community health services in Victoria, Australia. Based on the assessment results, this study confirmed the benefits of using a 360° subjective tool incorporating self and multiple colleague assessments in conducting management competency assessment and generating valuable evidence in guiding management competency development and the development of human resource management strategies at the organisational level. The 360° competency assessment (feedback) process not only confirmed the competency level of the assessment participants, but also identified managerial strengths and weaknesses of health service managers at individual, team and organisational levels. The paper suggests the investment of organisations in assisting their managers to improve their managerial competence by including the 360° competency assessment/ feedback process as one of the key steps. Key points: A 360° competency assessment tool was developed for healthcare managers. The tool has been tested on a group of mid‐level managers in community health services. The group was found to be reasonably competent for most competencies and behaviours. The assessments were able to distinguish areas of weakness and strength. The tool could identify low and top performing managers.